Knowledge, attitude and practice toward diabetes among the public in the Kingdom of Saudi Arabia: a cross-sectional study - Al-Wagdi, Bashayer Ebraheem; Al-Hanawi, Mohammed Khaled (Frontiers in Public Health, 2024)
Background The increasing adoption of sedentary lifestyles and cultural shifts has fostered unhealthy habits and decreased physical activity, consequently exacerbating the prevalence of diabetes. Diabetes is currently one of the top 10 diseases worldwide, contributing significantly to both mortality and morbidity. Since diabetes hinges on self-care, possessing the right knowledge, attitude, and habits related to the disease is paramount. This study, therefore, aims to examine the knowledge, attitude, and practice of diabetes among the population of Saudi Arabia. Methods The study utilized data from a cross-sectional study conducted via an online self-reported questionnaire among the general population of Saudi Arabia. The study primarily used univariate and multivariable regression data analyses. Univariate analysis was employed to compile social and demographic statistics frequencies, while One-way analysis of variance (ANOVA) was used to assess mean differences in knowledge, attitudes, and practices scores. Furthermore, a multivariable linear regression analysis was executed to identify factors associated with knowledge, attitudes, and practices. Results The mean score for diabetes knowledge was 17.79 (SD = 5.39, range: 0–29), with an overall accuracy rate of 61.34%. The mean attitude score for diabetes was 2.33 (SD = 1.91, range: 0–7), while the mean score for diabetes practices was 2.58 (SD = 1.28, range: 0–4). The multivariate analyses reveal distinct variations in knowledge, attitudes, and practices of diabetes among participants based on their gender, education, marital status, income, diabetes patient status, and having a medical field-related education. Conclusion High knowledge scores do not necessarily equate to positive attitudes and practices related to diabetes. There is need for intensified care and the implementation of specialized educational programs that emphasize the importance of having the right attitude and engaging in the good diabetes practices.